Zespoły, zespoły wirtualne a metody zarządzania nimi - Stankiewicz, Janina; Moczulska, Marta (The teams, virtual teams and methods of management of them, 2005)
In article was showed the character of the teams in modem forms of organization and their creating was showed on method favorable managements and working.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 619-626